Characteristics and application of S1-P1 nucleases in biotechnology and medicine - Koval, Tomáš; Dohnálek, Jan (Biotechnology advances, 2017)
3'-nucleases/nucleotidases of the S1-P1 family (EC 3.1.30.1) are single-strand-specific or non-specific zinc-dependent phosphoesterases present in plants, fungi, protozoan parasites, and in some bacteria. They participate in a wide variety of biological processes and their current biotechnological applications rely on their single-strand preference, nucleotide non-specificity, a broad range of catalytic conditions and high stability. We summarize the present and potential utilization of these enzymes in biotechnology and medicine in the context of their biochemical and structure-function properties. Explanation of unanswered questions for bacterial and trypanosomatid representatives could facilitate development of emerging applications in medicine.
Keywords: Fungal Proteins; nukleotidasy; Substrate Specificity; Single-Strand Specific DNA and RNA Endonucleases; mutační analýza DNA; Structure-Activity Relationship; cílená molekulární terapie; lidé; Antineoplastic Agents; protinádorové látky; DNA Mutational Analysis; biotechnologie; fungální proteiny; interakce hostitele a patogenu; vztahy mezi strukturou a aktivitou; Nucleotidases; Host-Pathogen Interactions; substrátová specifita; Biotechnology; Molecular Targeted Therapy; endonukleasy specifické pro jednořetězcové nukleové kyseliny; Humans